«Come i cirri delle piante rampicanti». Ruyer e lo spazio dell’impersonale - Cavedagna, Veronica; Poccia, Daniele (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
Even if the impersonal isn’t explicitly named in the earlier Ruyer, it may find an original proposition of this notion in his works. Thanks to his conception of space (and time), concerned with the ontological constitution of every structure or mechanism, Ruyer allows to go beyond anthropological implications of the impersonal. The aim of this proposal is to inspect and to develop some of the principal theoretical and ethical consequences of this earlier conception, also by comparison with the later Ruyer’s philosophy.